Find a particular solution using variation of parameters.
y'' + 3y' + 2y = 4e^x
yp = -y1 * INT (y2f(x)/W[y1,y2]) dx + y2 * INT (y1f(x)/W[y1,y2]) dx
The Attempt at a Solution
So, first I find the homogeneous solution, correct?
r2 + 3r + 2 = 0, so the roots are - 1 and -2, so
yh = c1 * e-x + c2 * e-2x
Then, I use the variation of parameters formula:
yp1 = -y1 * INT (y2f(x)/W[y1,y2]) dx
yp1 = y2 * INT (y1f(x)/W[y1,y2]) dx
Adding them together, yp = yp1 + yp2 = -10/3ex.
However, the answer is just 2/3ex, what I got for yp1.